(untitled) (Journal of Social Sciences Review, 2024)
Climate change is increasingly recognized as a major national security concern in Pakistan. The country faces many climate-related challenges, including rising temperatures, changing precipitation patterns, extreme weather events, and melting glaciers. These climate changes have a significant impact on various sectors such as agriculture, water resources, healthcare, and infrastructure. This article examines the impact of climate change on Pakistan’s national security, the threats and risks associated with environmental degradation, Pakistan’s current policy framework on climate change, and how Pakistan should address the climate crisis. Addressing these challenges requires urgent and concerted efforts to integrate climate change adaptation and mitigation strategies into national security policies to protect the well-being and stability of our people.